Depth-resolved and temperature-dependent analysis of phase formation mechanisms in selenized Cu-Zn-Sn precursors by Raman spectroscopy - Stroth, Christiane; Sayed, Mohamed H.; Schuster, Matthias; Ohland, Joerg; Hammer-Riedel, Ingo; Hammer, Maria S.; Wellmann, Peter; Parisi, Jürgen; Gütay, Levent (Journal of Materials Science: Materials in Electronics, 2016)
We present a study on the temperature and film depth dependent phase formation in Cu-Zn-Sn-Se thin films. Zn/Sn/Cu precursors were selenized at different temperatures, followed by depth-resolved Raman profiling. A high depth resolution for Raman analysis was achieved by a special sample preparation step using a focused ion beam to prepare shallow angle cross sections (SACS) of the absorber. Multi-phase structures were observed at low selenization temperatures with a first formation of the quaternary CuZnSnSe at only 250 °C and the existence of SnO in films annealed at 330 °C. At high selenization temperatures up to 560 °C CuZnSnSe was the main phase with some traces of ZnSe and a MoSe interface layer at the back contact. Furthermore, compositional gradients were investigated by scanning electron microscopy and energy dispersive X-ray spectroscopy measurements on sample cross sections. The combination of these results allows for observation of both elemental composition and phase composition of the films and their dynamics during the annealing procedur
Keywords: CZTSe; kesterite; Raman depth profiling; secondary phase formation; thin film solar cells